Penerapan Sistem Informasi Akuntansi Syariah untuk Mematuhi Etika Bisnis Rumah Sakit - Marina, Anna; Wahjono, Sentot Imam; Kurnoawati, Tri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The implementation of a sharia accounting information system (SIA) is needed for hospitals that are owned and whose patients are Muslim. Especially for hospitals that have been certified under sharia, it is imperative to own and operate a sharia SIA. The use of Islamic SIA can increase stakeholder satisfaction, especially hospital patients. The purpose of this paper is to explain how the Integrated IT Program can simultaneously improve hospital performance. We use Unified Modeling Language (UML) to develop Sharia AIS. The location of the observation in the context of community service is Muhammadiyah Hospital in Lamongan. The computerized AIS program is developed using UML while the database server uses MySQL and PHP as compilers. The approach to this report is qualitative based. Data were collected by interview, outside observation, and relevant documentation. Review The findings of this report indicate an increase in performance in terms of: new patient registration, invoice creation, printing of financial reports, and monitoring of accounts receivable. The four indicators show performance in terms of shorter working hours. SIA Syariah continues to be developed until all computerized systems are integrated for better compliance with hospital business ethics.